Day 3 Tue, October 17, 2017 2017
DOI: 10.2118/187640-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Condensate Blockage on Gas Well Deliverability - Part 1

Abstract: Predicting and assuring well deliverability is often an important concern during the development of gas-condensate reservoirs, especially offshore fields. In addition, production of gas is usually bound with long-term contracts where it is necessary to assure well deliverability for a long period. Undesirably, well deliverability in gas-condensate reservoirs can be impaired by the formation of a condensate blockage once the bottomhole flowing pressure drops below the dewpoint pressure. In this case, the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The results showed that gas production rate, gas composition, critical liquid saturation, absolute permeability, and rate scheme could very much affect condensate blockage, where the permeability and critical liquid saturation are most significant. Khazamet et al [24] studied gas well deliverability forecasting in a condensate reservoir using a compositional and modified black oil model. They investigated the impact of condensate blockage liquid drop-out by examining several fluid parameters such as the reservoir's absolute permeability (K), critical condensate saturation (S cc ), relative permeability shape, and endpoints (krg max , kro max ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that gas production rate, gas composition, critical liquid saturation, absolute permeability, and rate scheme could very much affect condensate blockage, where the permeability and critical liquid saturation are most significant. Khazamet et al [24] studied gas well deliverability forecasting in a condensate reservoir using a compositional and modified black oil model. They investigated the impact of condensate blockage liquid drop-out by examining several fluid parameters such as the reservoir's absolute permeability (K), critical condensate saturation (S cc ), relative permeability shape, and endpoints (krg max , kro max ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of heavy mercaptans from C4 and higher is also undesirable as they tend to hydrate formation. Since only C2-C3 mercaptans are to be present in the odorant, there arose a problem of removing or reducing the unwanted mercaptans [8][9][10].…”
Section: Introductionmentioning
confidence: 99%